Botswana : Technical Assistance Report-Report on National Accounts Mission. (IMF Staff Country Reports; Country Report, 2020)
This paper presents the Technical Assistance report National Accounts Mission in Botswana. As a result of recommendations made during the previous mission, Statistics Botswana (SB) have revised the release date for the rebase of national accounts estimates from March 2020 to December 2020 and updated the workplan accordingly. SB has made progress in finalizing the statistical frame and associated weights to compile gross value added (GVA) estimates for industries in the economic survey and estimates of GVA for the other industries. Once the business frame is determined, SB will have to reconcile the establishments that responded to the economic census ensuring that there is good coverage of industries as well as size of establishments. The previous mission strongly recommended that the release date for the rebased estimates be revised given the workload in rebasing the national accounts. The two temporary staff that have been with the national accounts for approximately 18 months as reported by the previous mission have been extended for a further two years. This is very positive news as they demonstrated a good understanding of the national accounts and a willingness to build their capacity.